A Late Pleistocene sea level stack, version 2 - Rachel M Spratt; Lorraine E Lisiecki (PANGAEA, 2025)
Late Pleistocene sea level has been reconstructed from ocean sediment core data using a wide variety of proxies and models. However, the accuracy of individual reconstructions is limited by measurement error, local variations in salinity and temperature, and assumptions particular to each technique. Here we present a sea level stack (average) which increases the signal-to-noise ratio of individual reconstructions. Specifically, we perform principal component analysis (PCA) on seven records from 0–430 ka and five records from 0–798 ka. The first principal component, which we use as the stack, describes ~80 % of the variance in the data and is similar using either five or seven records. After scaling the stack based on Holocene and Last Glacial Maximum (LGM) sea level estimates, the stack agrees to within 5 m with isostatically adjusted coral sea level estimates for Marine Isotope Stages 5e and 11 (125 and 400 ka, respectively). When we compare the sea level stack with the d18O of benthic foraminifera, we find that sea level change accounts for about ~40 % of the total orbital-band variance in benthic d18O, compared to a 65 % contribution during the LGM-to-Holocene transition. Additionally, the second and third principal components of our analyses reflect differences between proxy records associated with spatial variations in the d18O of seawater.